2008
DOI: 10.1016/j.acn.2007.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Prospective memory in HIV infection: Is “remembering to remember” a unique predictor of self-reported medication management?

Abstract: Optimal adherence to antiretroviral medications is critical to the effective long-term management of HIV infection. Although prospective memory (ProM; i.e., "remembering to remember") has long been theorized to play an important role in medication adherence, no prior studies have evaluated whether HIV-associated ProM impairment possesses unique predictive value in this regard. Results from this study demonstrate a robust association between ProM impairment and self-reported medication management in 87 HIV-infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
93
1
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(104 citation statements)
references
References 44 publications
7
93
1
3
Order By: Relevance
“…In addition, hippocampal dysfunction was noted both during encoding and retrieval of information among women with HIV in comparison to those without. 23 Importantly, self-reported cognitive and memory difficulties are associated with greater HIV symptom severity, 24,25 lower self-efficacy for medication management, 26 decline in instrumental activities of daily living, 27 and lower selfreported quality of life 25 among individuals with HIV.…”
Section: The Moderating Role Of Memorymentioning
confidence: 99%
“…In addition, hippocampal dysfunction was noted both during encoding and retrieval of information among women with HIV in comparison to those without. 23 Importantly, self-reported cognitive and memory difficulties are associated with greater HIV symptom severity, 24,25 lower self-efficacy for medication management, 26 decline in instrumental activities of daily living, 27 and lower selfreported quality of life 25 among individuals with HIV.…”
Section: The Moderating Role Of Memorymentioning
confidence: 99%
“…Deficits in EF and memory have been observed in children with PHIV, particularly those with advanced disease [2,12,13]. In adults with HIV, deficits in EF, retrospective memory (RM), and prospective memory (PM) have been noted, and some of these difficulties predict global neuropsychological impairment, difficulties in daily living, and medication nonadherence [14][15][16][17]. Understanding the specific nature and degree of contributions of memory and EF to academic and adaptive functioning in children with PHIV might guide the design of developmentally appropriate interventions and assist in targeting existing interventions to strengthen these skills [9,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The Memory for Intentions Screening Test, Children's Version (C-MIST), a measure of PM, was adapted for this study from the Memory for Intentions Screening Test (MIST) [23], a measure with demonstrated psychometric properties [24] that has been used in studies of adults with HIV [16,17]. The adaptation maintained the task format but included shorter time delays and modified instructions and activities, as appropriate for school-aged children.…”
Section: Predictors Of Primary Outcomesmentioning
confidence: 99%
“…This is unfortunate given the well-established associations between memory dysfunction and poor HIV-related outcomes [24,55] and lower perceived quality of life among individuals with HIV [21,56]. Further, because even moderate alcohol use may be harmful in this vulnerable population [1,57], such questions are relevant for the effective implementation of interventions that heavily tax memory, learning and attention.…”
Section: Introductionmentioning
confidence: 99%
“…Use of selfreport measures (i.e., meta-memory) may therefore provide a complimentary lens through which to examine the effects of problematic alcohol use on memory functioning among individuals with HIV. For instance, self-reported memory functioning has been shown to explain variance in selfreported medication management over and beyond that accounted for by neuropsychological test measures [55].…”
Section: Introductionmentioning
confidence: 99%